The Effects of Mechanical Milling and Nb-Based Additives on the Kinetics Sorption Properties of 2LiBH4-MgH2 - Marwan, Farhanah; Janot, Raphaël; Chotard, Jean-Noël (IPTEK Journal of Proceedings Series, 2015)
In this work, the effects of ball milling with different catalysts (including NbF5 and Nb2O5) on the hydrogen storage properties of 2LiBH4-MgH2 system were investigated. The increase of ball-milling time (from 5 min to 24 h) can reduce the crystallites size of MgH2 from 74 nm to 14 nm and decrease the dehydrogenation temperature of MgH2 from 390°C to 345°C. Among Nb-based catalysts, sample with NbF5 shows slightly better sorption kinetics than the one with Nb2O5, it can store reversibly about 9 wt.% of H2 in 24 h at 350°C, whereas more than 60 h are needed with Nb2O5 . This indicates that NbF5 is superior to Nb2O5 for improving the sorption kinetics of 2LiBH4-MgH2 system.